Uncertainty, quality, safety and accreditation in laboratory medicine - Plebani, Mario; Lippi, Giuseppe (Journal of Laboratory and Precision Medicine, 2017)
Laboratory diagnostics is conventionally defined as a science devoted to generate clinically useful information by analysing the concentration, composition and/or structure of aminoacids, proteins, lipids, carbohydrates, nucleic acids, cells, microorganisms and other exogenous compounds (i.e., drugs or toxics) in body fluids (1). The quality of test results generation, developing through a kaleidoscope of preanalytical, analytical and postanalytical activities, is a hallmark characterizing in vitro diagnostic testing, both from an analytical and safety standpoint (2). The former aspect mainly concerns the assurance that test results actually reflect the clinical condition in vivo, whilst the latter aspect especially regards patient safety, since diagnostic errors not only derange the clinical decision making and managed care, but will also jeopardize patient safety (3).